Response of wheat (Triticum aestivum) genotypes to different tillage practices for improving productivity and seed quality in eastern Indo-Gangetic plains of India - RAM, HARDEV; SINGH, RAJIV K; PAL, GOVIND; KUMAR, RAKESH; YADAV, M R; YADAV, T (The Indian Journal of Agricultural Sciences, 2017)
Quality seed, water, labour scarcity, rising cost of cultivation, diminishing farm profits and indecisive weather conditions are major challenges faced by the farmers under intensive tillage based conventional rice-wheat productionsystem of eastern Indo-Gangetic plains (IGP). To address these challenges from last few years, conservation agriculture (CA) based crop management practices are being developed, demonstrated and promoted in the region. The fieldexperiments were carried out during the winter (rabi) season of 2012-13 and 2013-14 at Indian Institute of Seed Science, Kushmaur, Mau, Uttar Pradesh to evaluate the effect of different tillage practices and genotypes on yield attributes, seed yield, seed quality, and economics of wheat (Triticum aestivum L.). Experiment was laid out in split-plot design consisting of 3 tillage systems, viz. Zero tillage (ZT), conventional tillage (CT) and raised beds (RB) as main-plots and 6 genotypes (KRL 213, HD 2733, PBW 550, HD 2967, KRL 210 and DBW 39) as sub-plots treatments and replicated thrice. Results revealed that among the tillage methods, the highest mean seed and biological yield (4.82 and 10.36 tonnes/ha) were found under ZT followed by CT (4.68 and 10.25 tonnes/ha) and least in RB (3.34 and 7.61tonnes/ha), respectively. Among the genotypes, HD 2967 showed significantly higher mean seed and biological yield (4.72 and 10.28 tonnes/ha) over KRL 210 (3.76 and 8.92 tonnes/ha), PBW 550 (4.10 and 8.95 tonnes/ha) and HD 2733 (4.24 and 9.48 tonnes/ha), respectively. However, genotypes KRL 213 (4.46 and 9.88 tonnes/ha) and DBW 39 (4.42 and 9.42 tonnes/ha) were found on par with HD 2967. The highest tillers/m2 as well as effective tillers/m2 was recorded under ZT system with HD 2967 genotype. However, the highest seeds/spike, spike length and test weightwere found under RB system with genotype HD 2967. There were no significant differences between the tillage systems concerning seed quality parameters, viz. germination %, seedling length, seedling dry weight, vigour index I and II. Moreover, the genotype HD 2967 showed significant difference among all seed quality parameters except germination (%) which was on par with HD 2733, KRL 213 and PBW 550. The maximum mean net returns was recorded under ZT (Rupees 75 500/ha) followed by CT (Rupees 65 600/ha) and RB (Rupees 41 100/ha). The total net gain in income due to adoption of ZT system wasÂ Rupees 17 300 andÂ Rupees 39 400/ha as compared to CT and RB, respectively.